Colour polymorphism and its function in Hippolyte obliquimanus: camouflage and resource use diversification - Duarte, Rafael Campos (2017)
This thesis addresses the mechanisms regulating the evolution and maintenance of colour polymorphism in the shrimp Hippolyte obliquimanus. It includes four chapters that illustrate, in an integrative approach, the ecological and behavioural consequences of different camouflage and habitat use strategies selected in main colour morphs. In the first chapter entitled Camouflage through colour change: mechanisms, adaptive value, and ecological significance, the physiological and structural mechanisms underpinning colour change, and hence camouflage, in different species were detailed within a general framework. Also in this section, both the adaptive value and the ecological and evolutionary implications of these processes were discussed. In the second chapter entitled Shape, colour plasticity, and habitat use indicate morph-specific camouflage strategies in a marine shrimp morph-specific colour change and habitat selection were investigated as potential mechanisms affecting camouflage efficiency and the natural distribution of H. obliquimanus colour morphs between macroalgal habitats formed by Sargassum furcatum and Galaxaura marginata. Moreover, morph-specific morphology and behavioural traits were also assessed. Shrimp showing a homogeneous coloration (H) changed colour when placed in colour-mismatching backgrounds and also exhibited a more robust shape associated to high substrate fidelity and specialization. On the other hand, striped translucent shrimp (ST) were not capable of colour change and showed high mobility, consistent with a more streamlined shape and a generalised use of algal habitats. In the third chapter entitled The adaptive value of camouflage and colour change in a polymorphic shrimp visual models and predation trials were used to test the adaptive value of camouflage and colour change of H. obliquimanus colour morphs against colour-contrasting macroalgae, which provide different levels of colour concealment. The low colour discrimination predicted by a visual model of a seahorse predator for pink shrimp against the red weed Galaxaura was directly translated to lower detection and consumption rates on this morph by captive seahorses in a laboratory experiment, demonstrating the high adaptive value of camouflage in this species. Finally, in the fourth chapter entitled Habitat-dependent niche partitioning between colour morphs of the algal-dwelling shrimp Hippolyte obliquimanus the trophic ecology of H and ST morphs when using Sargassum and Galaxaura habitats were assessed through stable isotope analysis. Morphs showed different isotopic signatures only in Galaxaura, where the supply of food resources are limiting, leading to a tropic niche diversification between H and ST shrimp and a probable relaxation of intra-specific competition. Conversely, in Sargassum, where resources are abundant, morphs coexistence is possible even without niche partitioning. Altogether, the results of this thesis contributed to a better understanding of the adaptive value and the underlying mechanisms controlling for the maintenance of colour polymorphism in H. obliquimanus. From both an ecological and evolutionary perspective, morph-specific strategies of camouflage and habitat use likely promote the stability of shrimp populations in a spatially heterogeneous and markedly seasonal habitat.